BLOG AS A TOOL OF E-LEARNING - Vyacheslav A. Starodubtsev; Antonina A. Kiseleva (Moscow Polytechnic University, 2016)
The functions of a disciplinary blog are considered in the integrated process of traditional learning and e-learning. The guiding possibilities of independent learning for graduate students and for teacher's professional training by using a blog as an educational and methodical complex are discussed. The main functions of the disciplinary blog are the following: providing with information and content, guiding of a user, stimulation of users' thinking, training and self-control, socialization, formation of students' outlook.